Flexible conductive polymer composites for smart wearable strain sensors. (23rd November 2020) - Zhou, Kangkang; Dai, Kun; Liu, Chuntai; Shen, Changyu
Abstract: Wearable strain sensors based on flexible conductive polymer composites (FCPCs) have attracted great attention due to their applications in the fields of human–machine interaction, disease diagnostics, human motion detection, and soft robotic skin. In recent decades, FCPC‐based strain sensors with high stretchability and sensitivity, short response time, and excellent stability have been developed, which are expected to be more versatile and intelligent. Smart strain sensors are required to provide wearable comfort, such as breathability, self‐cooling ability, and so forth. To adapt to the harsh environment, wearable strain sensors should also be highly adaptive to protect the skin and the sensor itself. In addition, portable power supply system, multisite sensing capability, and multifunctionality are crucial for the next generation of FCPC‐based strain sensor.